2018
DOI: 10.1093/mnras/sty1940
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate t-Mixtures-Model-based Cluster Analysis of BATSE Catalog Establishes Importance of All Observed Parameters, Confirms Five Distinct Ellipsoidal Sub-populations of Gamma Ray Bursts

Abstract: Determining the kinds of gamma-ray bursts (GRBs) has been of interest to astronomers for many years. We analyzed 1599 GRBs from the Burst and Transient Source Experiment (BATSE) 4Br catalogue using t-mixtures-model-based clustering on all nine observed parameters (T 50 , T 90

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 44 publications
2
25
2
Order By: Relevance
“…Early results indicate each of these strategies lead to comparable results in most cases. The use of k-means and Euclidean distances for applications such as in the case of clustering of GRBs [18], [20] is not always appropriate. Therefore, appropriate adjustments are required for handling non-spherically dispersed groups of data or datasets with unequal variances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early results indicate each of these strategies lead to comparable results in most cases. The use of k-means and Euclidean distances for applications such as in the case of clustering of GRBs [18], [20] is not always appropriate. Therefore, appropriate adjustments are required for handling non-spherically dispersed groups of data or datasets with unequal variances.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid methods of these two deletion schemes also exist. Yet another whole-data strategy [19], [20] clusters the complete records and classifies the incomplete records with rules based on the obtained grouping and a partial distance or marginal posterior probability approach. This scheme inherently assumes a missing-completely-at-random (MCAR) mechanism for the unobserved records and features.…”
Section: Introductionmentioning
confidence: 99%
“…Chattopadhyay et al (2007) using k-means partitioning method and the Dirichlet process of mixture modelling with also the same six parameters (T 50 , T 90 , F t , H 32 , H 321 and P 256 ) found also three kind of GRBs. Chattopadhyay & Maitra (2017) carried out multidimensional analysis of the BATSE data with six parameters but only for 1599 GRBs because of the assumption that if F 4 is missing the F t variable cannot be used (in a recent paper they published similar results (Chattopadhyay & Maitra 2018)). Because of the same reason, all 1929 bursts was analyzed only in a five-parameter space.…”
Section: Discussionmentioning
confidence: 99%
“…On this data set, K ‐means with the Jump statistic was initially shown to find three groups but careful reapplication found K to be indeterminate. MBC found five ellipsoidally dispersed groups in the log 10 ‐transformed data set. Rather than applying K ‐means on the log 10 ‐transformed features, we investigate a data‐driven approach to choose feature‐specific transformations before applying K ‐means.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses used only a few of the available features. The 25‐year‐old controversy between two or three GRB types is perhaps academic because careful model‐based clustering (MBC) and variable selection showed all available features as necessary. These studies also found five kinds of GRBs.…”
Section: Introductionmentioning
confidence: 99%